Elicitation effect on the production of asiaticoside and asiatic acid in shoot, callus, and cell suspension culture of Centella asiatica - M. Laxmi Krishnan, Arpita Roy, Navneeta Bharadvaja (Journal of Applied Pharmaceutical Science, 2019)
Centella asiatica is an important medicinal plant which contains various phytocompounds. Asiatic acid and asiaticoside are two major compounds which are responsible for its various pharmaceutical activities. The present study analyzes the effect of elicitor, i.e., methyl jasmonate on the synthesis of asiaticoside and asiatic acid (ATA) in shoot, callus, and cell suspension cultures of C. asiatica. A high-performance liquid chromatography analysis showed that the elicitation with 100 μM concentration of methyl jasmonate enhanced asiaticoside content by 69-fold in callus culture, 39-fold in shoot cultures, and ATA by 1.9-fold in cell suspension culture. Thus, elicitation with methyl jasmonate is an effective method of increasing the rate of biosynthesis of asiaticoside and ATA in plant cell cultures of C. asiatica.
Keywords: Centella asiatica, asiaticoside, asiatic acid, cell suspension culture, methyl jasmonate, shoot cultures.